Mind Matters - Ms. Savita Sharma; Shubam Ranga; Tushar Gupta; Yash (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This project is an innovative mobile application designed to address the mental health needs of children in the digital age. This app combines parental control features, activity tracking, mental health assessments, and a supportive chatbot powered by GPT API to create a holistic solution for parents and children. The app’s primary objectives include: ● Comprehensive Mental Health Assessment ● Real-time Text Sentiments Tracking ● Tasks Tracking ● Safe Browser ● Personalized Guidance and Resources ● Secured and Confidential Platform ● User Friendly